Early Macular Angiography among Patients with Glaucoma, Ocular Hypertension, and Normal Subjects - Shih-Chun Chao; Shang-Jung Yang; Hung-Chi Chen; Chi-Chin Sun; Chin-Hsin Liu; Chia-Yi Lee (Journal of Ophthalmology)
Purpose. To evaluate early macular circulation in open-angle glaucoma (OAG), normal-tension glaucoma (NTG), ocular hypertension (OHT), and healthy subjects via optical coherence tomography angiography (OCTA). Methods. A retrospective cross-sectional study was conducted. Medical records were reviewed, and the patients who received OCTA examinations were divided into the OAG, NTG, OHT, and normal groups. The ophthalmic data including best-corrected visual acuity, spherical equivalent, intraocular pressure, central corneal thickness, central foveal thickness, visual field deviation, retinal nerve fiber layers thickness, and ganglion cell complex thickness were obtained from medical documents. For the macular area, the superficial vessel density (VD), deep VD, foveal avascular zone (FAZ), flow area of the outer retina, and flow area of the choriocapillaris were measured via OCTA and analyzed using the default vascular density analysis program in the same OCTA device. Results. A total of 70 eyes from 70 patients were analyzed in the current study. Significant differences in the intraocular pressure, central corneal thickness, visual field deviation, retinal fiber layer thickness, and ganglion cell complex thickness were observed in the patients in the glaucoma group at their last visits. The OAG and NTG groups evinced a lower superficial VD than did the control group, while the NTG group had a lower deep VD than the control group. The NTG group also had a larger FAZ than did the OHT group. The flow area of the outer retina in the OAG group was low relative to those of the OHT and control groups. No difference in choriocapillaris perfusion was observed among the groups. Conclusion. The OAG and NTG patients demonstrated impaired vasculature before significant disease development could be observed. Furthermore, the differences in macular circulation may be associated with differences in the courses of disease between the glaucoma and OHT patients.